2016
DOI: 10.1371/journal.pone.0152070
|View full text |Cite
|
Sign up to set email alerts
|

Making a Bad Situation Worse: An Invasive Species Altering the Balance of Interactions between Local Species

Abstract: Biological invasions pose a significant threat to biodiversity, especially on oceanic islands. One of the primary explanations for the success of plant invaders is direct suppression of competitors. However, indirect interactions can also be important, although they are often overlooked in studies on biological invasion. The shrub Leucaena leucocephala is a widespread island invader with putative allelopathic effects on the germination and growth of other species. We quantified the impact of Leucaena on plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, as Leucaena spp. can become an invasive alien species in certain areas, it must be managed with caution (Chiou et al, 2016;Mello and Oliveira, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, as Leucaena spp. can become an invasive alien species in certain areas, it must be managed with caution (Chiou et al, 2016;Mello and Oliveira, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been no clear explanation for the suppression of L. leucocephala on native plant species. However, it was observed that the survival and growth of a native woody plant species, Erythrina velutina Willd., was suppressed by the presence of L. leucocephala in the field experiments under relatively controlled conditions [34]. The experiments under controlled conditions may illuminate the possible involvement of light and other environmental factors and suggest the involvement of other factors, such as allelopathy, in the suppression.…”
Section: Field Observationmentioning
confidence: 70%
“…leucocephala threatens native vegetations and biodiversity in the invaded areas [11,27,34]. The species richness in L. leucocephala invaded areas was lower than that in its unin-vaded areas, and the establishment of the native plant species was hardly observed in the L. leucocephala invaded areas [31,34,45,46]. Seedling establishment of native plant species in L. leucocephala plantations was also less [45].…”
Section: Field Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…A shift in resource availability during succession can cause a shift in community composition and structure from secondary to old-growth forest [ 4 ]. Non-native species can play an important role during succession [ 5 ], as they often have strategies of rapid resource uptake and use and can, in some cases, outperform native species [ 6 , 7 ]. A challenge is to understand the role of non-native species in the community processes because they can potentially become invasive [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%